Tumor Necrosis Factor-α is Associated with Positive Lymph Node Status in Patients with Recurrence of Colorectal Cancer – Indications for Anti-TNF-α Agents in Cancer Treatment. (2010) - Grimm, M.; Lazariotou, M.; Kircher, S.; Höfelmayr, A.; Germer, C. T.; von Rahden, B. H. A.; Waaga-Gasser, A. M.; Gasser, M.
Abstract : Introduction : The progressive growth of malignancies is accompanied by a decline in the immune response through mechanisms which are poorly understood. Apoptosis and induction of inflammation by tumor released cytokines as tumor escape mechanisms have been proposed to play an important role in colorectal carcinogenesis. Methods : Expression of Tumor necrosis factor-alpha (TNF- α ) was analyzed in colorectal cancer specimen and the cancer cell line HT-29 by immunohistochemistry and RT-PCR. TNF- α expression on protein and mRNA level were correlated with clinical characteristics and impact on survival. TNFR-1 was co-labelled with TNF- α and CD8+ cytotoxic T cells in immunofluorescence double staining experiments. Results : 94% ( n =98/104) of the patients with CRC expressed TNF- α . High TNF- α expression was significantly associated with positive lymph node stage and recurrence of the tumor. Multivariate analysis revealed high TNF- α expression as an independent prognostic factor. Immunohistochemistry was correlated with RT-PCR results (τ=0.794). Immunofluorescence double staining experiments revealed increased TNFR-1 expression by CD8+ cells. Conclusion : TNF- α expression by tumor cells may be an efficient immunological escape mechanism by inflammation-enhanced metastases and probably by induction of apoptosis in tumor-infiltrating CD8+ immune cells resulting in a down regulation of the tumoral immune response. Our data support the role of tumor-derived TNF- α expression as an important promoter of tumoral immune escape mechanisms and malignant progression, and suggest that analysis on either protein (immunohistochemistry) or RNA level (RT-PCR) can be used effectively in this respect. Targeting TNF- α may be a promising option, especially in cases with high TNF- α expression and positive lymph node metastases.